FUNGSI KELOMPOK TANI DALAM PENYEDIAAN SARANA PRODUKSI PADI SAWAH DI DESA WUNGKOLO KECAMATAN WAWONII SELATAN KABUPATEN KONAWE KEPULAUAN - Asriman Asriman; Awaluddin Hamzah; Mardin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
Agricultural production facilities play a pivotal role in the field of farming, as they have the capacity to enhance productivity, quality, and efficiency of agricultural land. However, farmers often encounter challenges in acquiring the necessary means of production, including fertilizers, seeds, and pesticides, during the agricultural cycle. This study aims to examine the function of farmer groups in the provision of production facilities in paddy rice farming in Wungkolo Village, South Wawonii District, South Konawe Regency. The selection of informants was conducted using a purposive sampling method. The study's informant pool comprised 10 individuals. Data were collected through in-depth interviews guided by a list of questions related to the subject under study. To bolster the findings, observational and documental methods were employed. The analysis of the collected data was conducted through a descriptive and qualitative approach, encompassing data reduction, data presentation, and conclusion drawing. The results indicated that farmer groups' provision of production facilities has been ineffective. Evidence of this shortcoming is apparent in the inadequate provision of fertilizers and pesticides, both in terms of type and amount, which fall short of meeting farmers' needs. Conversely, farmer groups have demonstrated efficacy in the provision of seeds, as evidenced by the provision of the appropriate type of seeds, sufficient quantities, and the facilitation of this process by the Agriculture Office and Field Agricultural Extension Officers.